ANALISIS SOAL PILIHAN MAJEMUK MITIGASI BENCANA KELAS XI: TINGKAT KESULITAN, PEMBEDA, DAN EFEKTIVITAS MELALUI PLATFORM DIGITAL - Anisa Nurhidayati; Aswaly Dinove Chandra; Muhammad Rizki Parhan; Muhamad Rizky Setiawan; Rafi Mahesa Akbar Sisnawar; Mamat Ruhimat; Rahayuni Tyas Pratiwi; Dina Siti Logayah (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2025)
This research was conducted to analyze the Geography subject matter questions for 11th-grade students. The population and sample are the 11th-grade students of SMA Negeri 3 Cimahi, based on the students' understanding of disaster mitigation material in the Geography subject according to the current curriculum. Technique Data collection in this study was conducted through a digital questionnaire method designed interactively and gamified using the Quizizz platform, and the analysis was carried out using Microsoft Excel. The results and discussion of this article are presented in several subsections to facilitate the understanding of the content and research findings. The analysis includes five aspects, namely the Validity Test to ensure that the questions used truly measure what they are supposed to measure, so that the measurement results are more accurate and reliable.